Development of the pediatric neuro-oncology services assessment aid: An assessment tool for pediatric neuro-oncology service delivery capacity - Rajagopal, R (2024)
Background. To enhance the quality of care available for children with central nervous system (CNS) tumors across the world, a systematic evaluation of capacity is needed to identify gaps and prioritize interventions.To that end, we created the pediatric neuro-oncology (PNO) resource assessment aid (PANORAMA) tool. Methods. The development of PANORAMA encompassed 3 phases: operationalization, consensus building, and piloting. PANORAMA aimed to capture the elements of the PNO care continuum through domains with weighted assessments reflecting their importance. Responses were ordinally scored to reflect the level of satisfaction. PANORAMA was revised based on feedback at various phases to improve its relevance, usability, and clarity. Results. The operationalization phase identified 14 domains by using 252 questions.The consensus phase involved 15 experts (6 pediatric oncologists, 3 radiation oncologists, 2 neurosurgeons, 2 radiologists, and 2 pathologists). The consensus phase validated the identified domains, questions, and scoring methodology.The PANORAMA domains included national context, hospital infrastructure, organization and service integration, human resources, financing, laboratory, neurosurgery, diagnostic imaging, pathology, chemotherapy, radiotherapy, supportive care, and patient outcomes. PANORAMA was piloted at 13 institutions in 12 countries, representing diverse patient care contexts. Face validity was assessed by examining the correlation between the estimated score by respondents and calculated PANORAMA scores for each domain (r = 0.67, P < .0001). Conclusions. PANORAMA was developed through a systematic, collaborative approach, ensuring its relevance to evaluate core elements of PNO service capacity. Distribution of PANORAMA will enable quantitative service evaluations across institutions, facilitating benchmarking and the prioritization of interventions.